How changing environments alter the microbial composition and ecological response in marine biofilms: a mini review. Issue 1 (31st December 2023) - Ugya, Adamu Yunusa
ABSTRACT: Marine environments are made up of different types of surfaces with different physicochemical and biological features. The aim of this study is to review literatures on how stress induced by changing marine environment alters microbial biofilm niches and triggers ecological responses. The present review show how Greenhouse gas emissions (GHGE) and climate change causes alteration of the marine environment leading to temperature change, acidification and increase in deoxygenation of marine environment. The mini review also shows the processes involve in microbial biofilms formation in marine environment. The mini review shows the role play by marine biofilm in the sustainability of marine environment. The role of marine biofilm in marine carbon sequestration was also discussed because carbon is the most important tool for the building of biomolecules such as nucleic acids, proteins, carbohydrates, and lipids. The present study report processes involve in marine nitrogen deposition and the role of marine biofilm in the process of nitrogen transformation and deposition. The effect of GHGE on ecological response in marine biofilms was also fully explained in this mini review..